Marco legal de la tecnología digital y la privacidad de los datos - Cornejo Ramon, Widinson Arturo (2025)
The study aimed to analyze the effectiveness and challenges of Ecuador's legal framework on technology in protecting data privacy against technological advancements in a globalized digital environment. The methodology was mixed: it had a qualitative approach due to the analysis of theoretical frameworks and a quantitative approach through the application of a Likert-scale survey to 20 lawyers from the Guayas Bar Association. The results indicated that 35% of respondents believed the regulations are unclear in guaranteeing privacy in the digital environment, 55% were unsure whether the law aligns with international standards, and 40% considered that the institutions responsible for enforcing the regulations do not act efficiently and rigorously. Additionally, 45% of respondents stated that the mechanisms for reporting privacy violations are ineffective. Based on these findings, it was concluded that while the Organic Law on Personal Data Protection and its regulations establish solid principles, there are challenges in their implementation and enforcement.